Elektrolitik suyun bakteriyel enzim üretimine etkisi - Tunabay, Zübeyde (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2009)
Bu çalışmada elektrolitik suyun; Leuconostoc mesenteroides B?512 FMC-13Glc, yerel izolat Staphylococcus aureus, Bacillus subtilis ATCC 6633 mikroorganizmalarının büyümeleri ve bu mikroorganizmalar tarafından üretilen dekstransükraz, lipaz ve a-amilaz aktiviteleri üzerine olan etkinliği çalışıldı. Elektrolitik su, çeşme suyunun tuz eklemeden iki farklı cihaz ile elektroliz edilmesiyle hazırlanmıştır.Elektrolitik su ile hazırlanan besiyerlerde mikroorganizmaların saf suyla hazırlanan besiyerlerden daha iyi büyüdüğü ve daha fazla enzim ürettikleri (dekstransükraz, lipaz ve a-amilaz) bulunmuştur. En iyi sonuç Staphylococcus aureus' da elde edilmiştir ve lipaz aktivitesinde 50 ile 100 kat arasında artış bulunmuştur.Bakteri büyümesi ve enzim üretimindeki artışlar, elektrolitik su ve saf suyla hazırlanan besiyerlerin ORP ve pH değerleri aynı olduğundan, elektrolitik suyun küçük molekül kümeleriyle açıklanmıştır. Küçük molekül kümeli su, besinlerin mikroorganizmalara saf sudaki yayılmaya göre daha hızlı yayılmalarını sağlamaktadır. Sonuçlar mikrobiyel üretimlerde geniş kullanım alanları sağlamaktadır.

In this study, the effect of electrolytic water on the growth of such bacteria as Leuconostoc mesenteroides B?512 FMC-13Glc, a local isolate Staphylococcus aureus, and Bacillus subtilis ATCC 6633 and production of dextransucrase, lipase and a-amylase by these microorganisms were studied. Electrolytic water was prepared by electrolysis of tap water without addition of salts in two different commercial apparatus.It was found that microorganisms studied grew better and produced more enzymes (dextransucrase, lipase, and a-amylase) in broth medium prepared using electrolytic water than in broth prepared using distilled water. The best result was obtained using Staphylococcus aureus and the increase in lipase activity was between 50 to 100 folds.It is proposed that a possible explanation for increase in both bacterial growth and enzymic production is due to the small cluster size of water in electrolytic water since pH values and oxidation-reduction potentials of broth mediums using distilled and electrolytic water were the same. Small cluster sized water could make diffusion of nutrients into microorganism much faster than diffusion of nutrients in distilled water. The results obtained could find wide applications in microbial productions.
The effect of electrolytic water on the production of bacterial enzyme
Keywords: Biyokimya; Biochemistry